The Impact of Social Media Influencers’ Source Attractiveness, Source Trustworthiness, Source Expertise, and Parasocial Interaction Towards Consumer Purchase Intention in the Case of Cimory Indonesia - Antonia Karen Wadoe; Kimberly Nikita (iBuss Management, 2022)
Nowadays, the digital world is thriving. One of the most compelling phenomena is the rise of social media as an effective communication medium, where individuals around the globe connect to one another – not excluding businesses and enterprises who utilize the blooming momentum of social media as their way to stay connected to their consumers. To do so, businesses and enterprises are collaborating with social media influencers to advertise their products. This study would like to further analyze the impact of source attractiveness, source trustworthiness, source expertise, and parasocial interaction of social media influencers on purchase intention which is being applied in the social media marketing strategy of Cimory Indonesia. The researchers use simple random sampling as the research’s design, which assumes that each element has an equal chance of being part of the sample. The data for the research was collected through online questionnaires with a total of 150 eligible respondents. The collected data is then processed by using Multiple Linear Regression through IBM SPSS Statistics. The results showcase that source attractiveness, source trustworthiness, source expertise, and parasocial interaction of social media influencers have positive significant relationship to purchase intention in the case of Cimory Indonesia simultaneously and individually.Keywords: Source attractiveness, Source trustworthiness, Source expertise, Parasocial interaction, Social media influencer, Purchase intention